Recent Advances in Heterogeneous Catalysis for Ammonia Synthesis - Marakatti, Vijaykumar S.; Gaigneaux, Eric M. (ChemCatChem, 2020)
Even after a century, ammonia (NH3) synthesis from nitrogen and hydrogen through Haber‐Bosch process is still energy intensive. Even with recently introduced second generation Ru based catalysts with superior performance over commercial Fe based catalysts, there is still place for upgrading with new approach using advanced materials in catalyst formulation. The alkali and alkaline metal promoted Ru supported carbon and metal oxide catalyst attracted attention at initial stage and extensively studied for NH3 synthesis in the 20th century. Until recently, advanced materials such as electrides, hydrides, nitrides, oxides and oxy‐hydrides‐nitrides studied as support and active component of catalyst fascinated much attention, with milder reaction conditions for NH3 synthesis. These materials with unique properties of reversible storage of electrons, hydrides, nitrides and oxygen vacancies enrich electron density on Ru catalyst and cleave N≡N bond with very low activation energy (<60 kJ/mol). The mechanistic understanding of these materials leads to the fact that activation N≡N bond is no more rate‐determining step (RDS). Instead, formation of N−H bond is RDS, pushing towards an innovative research directions and scientific basis for development of new catalysts. Enormous maturation of experimental and theoretical methods with improved precession over worldwide research effort helped in gaining a fundamental understanding of these materials in NH3 synthesis. The most of Ru supported on these advanced materials were better in performance compared to benchmark Cs−Ru/MgO and Ru/AC catalysts in NH3 synthesis. Insights on these materials and their mechanism are covered in this review, which digs towards finding a realistic catalyst for NH3 synthesis. TOC: This review will give insights on recent development in advanced materials such as electrides, hydrides, nitrides, oxides and oxy‐hydrides‐nitrides as support and active component of Ru based catalyst in NH3 synthesis at milder reaction conditions. Electrides, hydrides, nitrides and oxides with their promising unique properties of reversible electron, hydride, nitride and oxide vacancies storage have tremendously improved Ru based catalysts efficiency. Perceptions on these materials and their mechanism digs towards finding a realistic catalyst for NH3 synthesis.